Characterized cis-FeV(O)(OH) intermediate mimics enzymatic oxidations in the gas phase - Borrell, Margarida; Andris, Erik; Navrátil, Rafael; Roithová, Jana; Costas, Miquel (Nature communications, 2019)
FeV(O)(OH) species have long been proposed to play a key role in a wide range of biomimetic and enzymatic oxidations, including as intermediates in arene dihydroxylation catalyzed by Rieske oxygenases. However, the inability to accumulate these intermediates in solution has thus far prevented their spectroscopic and chemical characterization. Thus, we use gas-phase ion spectroscopy and reactivity analysis to characterize the highly reactive [FeV(O)(OH)(5tips3tpa)]2+ (32+) complex. The results show that 32+ hydroxylates C-H bonds via a rebound mechanism involving two different ligands at the Fe center and dihydroxylates olefins and arenes. Hence, this study provides a direct evidence of FeV(O)(OH) species in non-heme iron catalysis. Furthermore, the reactivity of 32+ accounts for the unique behavior of Rieske oxygenases. The use of gas-phase ion characterization allows us to address issues related to highly reactive intermediates that other methods are unable to solve in the context of catalysis and enzymology.
Keywords: Iron; Oxygenases; Oxidation-Reduction; Catalysis; Iron Compounds; sloučeniny železa; železo; katalýza; oxygenasy; oxidace-redukce